How would you solve the equation y=3x-11 with 0=6x-2y-22 using systems by substitution​? Pls i need help with this

Question

How would you solve the equation y=3x-11 with 0=6x-2y-22 using systems by substitution​? Pls i need help with this

in progress 0
Eirian 6 months 2021-08-14T05:28:21+00:00 2 Answers 1 views 0

Answers ( )

    0
    2021-08-14T05:29:30+00:00

    Answer:

    This is the answer

    x=0 y=-11 (0,-11)

    Hope I helped! 🙂

    Step-by-step explanation:

    0
    2021-08-14T05:29:42+00:00

    Answer:

    x=0 y=-11 (0,-11)

    Step-by-step explanation:

    1. take what y equals (3x-11) and plug it in for y in the second equation

    Should look like this: O= 6x-2(3x-11)-22

    2. Then distribute O=6x-6x+22-22

    3. Then combine like terms O= 0 the 22’s cancel out as well as the x’s

    x= 0

    4. plug 0 in for x in the first equation y=3(0)-11

    5. y= -11

    6. x=0 y=-11 (0,-11)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )